Toponomastics, interdisciplinarity and teaching: essays on pedagogical proposals of the BNCC - Alexandre, Anna Inez (2024)
This article aims to reflect and suggest how the toponymic lexicon can be used in schools. Therefore, it presents a theoretical approach to Toponomastics (DICK, 1990a, 1990b; TRAPERO, 1995, 1999; CABRERA, 2002-2003) and its interdisciplinary character and its relation to education. In addition, a study of competencies in languages and their technologies, as well as Social and Applied Human sciences, provided for in the Brazilian Common National Curricular Base (BNCC), is presented. It is a qualitative, documentary research. It proposes some interdisciplinary pedagogical workshops to approach the names of places in school (CARLOS, 2007; THEISEN, 2008; FAZENDA, 2012), aimed at high school and related to the competencies presented by the BNCC. The study of the document has shown that interdisciplinarity is the proposed pedagogical approach and organize principle of the curriculum for this level of basic education. The choice to present toponomastic studies in the form of workshops is because they are group activities that promote the linking of knowledge between school subjects such as Portuguese, History and Geography, and also contribute to the development of the skills and abilities envisioned by the BNCC.